2014
DOI: 10.4137/cmped.s13505
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric Morbidity among Street Children in Duhok

Abstract: BACKGROUNDDue, in part, to family constraints in dealing with the economical burden of raising a family, a wave of street children is sweeping the developing world. Such children are prone to both somatic and mental illnesses. This is the first ever study that has been conducted to explore the psychopathology among street children in the Duhok Governorate.METHODSThe study was conducted between March 2004 and May 2005 in Duhok City among street children who attended the Zewa Center—the only center for street ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(24 citation statements)
references
References 10 publications
(12 reference statements)
0
20
0
4
Order By: Relevance
“… 19 , 28 , 42 , 43 Taib and Ahmad in their study in 2014 identified particular psychiatric disorders in street children like schizophrenia and others. 55 The following psychiatric disorders among street children in Africa were reported: depression, hopelessness and suicide ideation, among others. Risk factors like stress and trauma faced by street children were only described in the studies and no standardized diagnostic tools were used in measuring post-traumatic stress disorder, which was described in the studies.…”
Section: Resultsmentioning
confidence: 99%
“… 19 , 28 , 42 , 43 Taib and Ahmad in their study in 2014 identified particular psychiatric disorders in street children like schizophrenia and others. 55 The following psychiatric disorders among street children in Africa were reported: depression, hopelessness and suicide ideation, among others. Risk factors like stress and trauma faced by street children were only described in the studies and no standardized diagnostic tools were used in measuring post-traumatic stress disorder, which was described in the studies.…”
Section: Resultsmentioning
confidence: 99%
“…worked on the streets because of the economic needs and pressure on their families. It illustrated higher rates of anxiety and depression among these children (Taib & Ahmad, 2014).…”
Section: Total 120 120mentioning
confidence: 88%
“…countries. It is believed to be an index related to poverty, families with low literacy level and large extended families (Taib & Ahmad, 2014).…”
mentioning
confidence: 99%
“…The few studies on psychopathology of homeless or street children in developing countries include a Turkish study [ 48 ] that found 61% of street children had at least one psychiatric disorder while a Ghanaian study reported that as high as 87% of homeless youth showed moderate to severe psychosocial symptoms [ 9 ]. In their study which assessed 112 Burundian male children, Crombach et al provide evidence that psychopathology among children who had spent parts of their lives on the streets was associated with exposure to violence [ 19 ].…”
Section: Introductionmentioning
confidence: 99%